2009
DOI: 10.1086/605961
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Species Diversity on Temporal Stability in Single‐Trophic and Multitrophic Communities

Abstract: The question of how species diversity affects ecological stability has long interested ecologists and yet remains largely unresolved. Historically, attempts to answer this question have been hampered by the presence of multiple potentially confounding stability concepts, confusion over responses at different levels of ecological organization, discrepancy between theoretical predictions, and, particularly, the paucity of empirical studies. Here we used meta-analyses to synthesize results of empirical studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
176
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(216 citation statements)
references
References 54 publications
29
176
10
1
Order By: Relevance
“…But theory and data both support greater temporal stability of a community property like total biomass at higher levels of diversity. Five syntheses have 40 summarized how diversity impacts variation of ecosystem functions through time [38][39][40][41][42] , and these have shown that total resource capture and biomass production are generally more stable in more diverse communities. The mechanisms by which diversity confers stability include overyielding, statistical averaging, and compensatory dynamics.…”
Section: There Is Mounting Evidence That Biodiversity Increases the Smentioning
confidence: 99%
“…But theory and data both support greater temporal stability of a community property like total biomass at higher levels of diversity. Five syntheses have 40 summarized how diversity impacts variation of ecosystem functions through time [38][39][40][41][42] , and these have shown that total resource capture and biomass production are generally more stable in more diverse communities. The mechanisms by which diversity confers stability include overyielding, statistical averaging, and compensatory dynamics.…”
Section: There Is Mounting Evidence That Biodiversity Increases the Smentioning
confidence: 99%
“…Finally, to compute deterministic invariability I D , we must solve (11). Here this formula takes the simple form of…”
Section: Comparison Of Stability Measuresmentioning
confidence: 99%
“…[10][11][12][13]. Although theoretical studies have also considered stability measures based on variability [14][15][16], the link with resilience is not obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Both empirical and theoretical studies indicate that diversity enhances stability; however, aspects of stability can be affected differently, and these relationships play out in multiple ways in different ecosystems (e.g., see references 101, 139, 156, 292, 325-327, 334, 340, 351, and 375). For example, it has been shown that while diversity increases total community stability, it decreases the stability of populations within a community (156,188,340). These ecological concepts have been studied in a wide range of communities (Table 2).…”
Section: Resistance and Resiliencementioning
confidence: 99%